Diego - Winter, Jonah, 1962-; Winter, Jeanette (New York : Knopf : Distributed by Random House, 1991)
Discusses the childhood of Diego Rivera and how it influenced his art.
"In English and Spanish."
"In English and Spanish."
Keywords: Rivera, Diego, -- 1886-1957 -- Childhood and youth -- Juvenile literature; Rivera, Diego, -- 1886-1957 -- Childhood and youth; Painters -- Mexico -- Biography -- Juvenile literature; Artists -- Juvenile literature; Painting, Modern -- Mexico -- Juvenile literature; Art appreciation -- Juvenile literature; Bilingual books